Feel Beauty, Trust, Buy Again! Investigating Key Drivers of Customer Repurchase Intention in Beauty Brands Industry (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The skincare industry in Indonesia is experiencing rapid growth, primarily driven by the significant development of e-commerce and increased consumer awareness of self-care. This surge has resulted in intense competition among brands. This comparative study aims to analyze the role of trust as a mediating variable that connects price fairness, celebrity endorsements, and e-WOM to repurchase intentions for two brands: Somethinc (a science-based brand) and Wardah (a halal-based brand). A quantitative research method was used, involving a survey with a 5-point Likert scale distributed to 150 millennials and Gen Z respondents in Semarang City. The data were analyzed using PLS-SEM (SmartPLS). The findings reveal that both celebrity endorsements and trust have a significant impact on repurchase intentions for both brands. In contrast, price fairness and e-WOM do not have a significant direct effect on either brand. However, the study shows that trust effectively mediates the influence of price fairness, celebrity endorsements, and e-WOM on repurchase intentions. This underscores the vital role of trust in enhancing customer loyalty to Somethinc and Wardah. These findings suggest that strengthening brand trust in skincare products can significantly boost customer loyalty.